The Contributions of Pandemic Severity, Government Stringency, Cultural Values and Internet Usage to Post-traumatic Stress Disorder During the COVID-19 Pandemic: An Analysis of Data From 35 Countries - Rajkumar, Ravi Philip (Frontiers in Sociology, 2022)
Emergent symptoms of post-traumatic stress disorder (PTSD) have been frequently reported in the context of the COVID-19 pandemic, and may affect up to 17-18% of individuals. There is preliminary evidence that pandemic severity, cultural values, restrictions imposed by governments, and Internet usage may all influence the emergence of PTSD symptomatology. In this study, possible linear- and non-linear associations between these factors and the prevalence of PTSD symptoms across 35 countries were examined based on data from existing research. Evidence was found for a positive logarithmic relationship between the COVID-19 case-fatality ratio and PTSD (p = .046), a positive logarithmic relationship between power distance and PTSD (p = .047), and a trend towards a negative quadratic association with Internet usage (p = .051). No significant cross-national effect was observed for government restrictiveness. These findings suggest that strategies aimed at minimizing COVID-19 deaths, and at ensuring equitable access to essential resources, may be of use in reducing the emergence of PTSD symptoms at a population level during this pandemic.